Reproduction and animal health - Walters, Charles, 1926-; Fry, Gearld, 1941- (Austin, Tex. : Acres U.S.A., 2003)
This book represents the combined experience and wisdom of two leaders in sustainable cattle production. Gearld Fry offers a lifetime of practical experience seasoned by study and observations as well as interviews with thousands of eco-farmers and consultants over the past four decades. The result is an insightful book that is practical in the extreme, yet eminently readable. In this book you will learn how to "read" an animal; what linear measurement is; why linear measurement selects ideal breeding stock; the nuances of bull fertility; the strengths of classic cattle breeds; the role of pastures; and the mineral diet's role in health.--COVER.
Reflections of a cowman --Reading the animal --The mandate to measure --Bull fertility --Classic cattle --Pastures --The mineral diet --Cowboy arithmetic --The industry.
Includes index.
Keywords: Cattle -- Reproduction; Cattle -- Breeding; Cattle -- Fertility; Cattle -- Feeding and feeds